Healthcare Workforce Management and Economic Performance : A Systematic Review of Human Resource Strategies - Syifi Fauziyah; Istiqomah Istiqomah; Yusuf Efendi (Jurnal Visi Manajemen, 2025)
Healthcare workforce management has become increasingly critical in determining organizational economic performance and long-term sustainability. This systematic review examines the relationship between human resource strategies in healthcare settings and their impact on economic outcomes, with particular attention to the effectiveness of workforce planning, recruitment optimization, employee retention, and performance management systems. The objective of this review is to synthesize current evidence on healthcare workforce management practices and their influence on economic performance indicators across various healthcare organizations. A systematic literature review was conducted using multiple academic databases, including PubMed, Scopus, and Web of Science. Studies published between 2019 and 2024 that focused on healthcare workforce management and its association with economic performance were selected based on predefined inclusion and exclusion criteria. A total of 45 peer-reviewed articles met the eligibility requirements and were included in the final analysis. The findings reveal that strategic human resource management practices significantly correlate with improved economic outcomes in healthcare organizations. Institutions implementing comprehensive workforce management approaches demonstrated a 15–25% improvement in cost-effectiveness, resource utilization, and operational efficiency. Moreover, effective healthcare workforce management was shown to directly enhance organizational performance by reducing staff turnover costs, improving employee productivity, and strengthening service delivery quality. This review concludes that integrated and evidence-based human resource strategies are essential for healthcare systems aiming to achieve sustainable economic growth and resilience in the face of evolving healthcare challenges.